(untitled) (International journal of artificial intelligence, 2026)
This article explores the use of figurative language in the literary works of Mark Twain and Xudoyberdi To‘xtaboyev, focusing on how metaphor, irony, hyperbole, and symbolism function within different cultural and historical contexts. Using a qualitative textual analysis, the study demonstrates that although the two writers belong to distinct literary traditions, figurative language serves a similar purpose in their works: it humanizes social critique, enhances narrative engagement, and reflects the worldview of ordinary people. The research follows the IMRAD structure and aims to provide a student-level yet academically reliable comparative analysis.